The Right to Manage Emergent Land on the Riverbank - Amir, Latifah; Helmi, Helmi; Budhiartie, Arrie; Nuriyatman, Eko (Universitas Lampung, 2024)
Management rights over emergent land on the banks of the Batanghari River Watershed in Penyengat Rendah District, Jambi City have been practiced by the local community for generations without formal ownership as of this study. This article examines the legality of land tenure under Indonesian law and the rights to manage land emerging along the Batanghari riverbanks, aiming to advise the local government on the crucial need for legal recognition of these rights. Utilizing an empirical research method involving direct community engagement, the study finds that community management of this land is driven by longstanding residency and utilization, the scarcity of available land for agriculture in Jambi City supporting the local economy, high land prices, and historical reliance on riverbank land use. Despite continuous management, these activities lack permanent legal status as outlined in Article 16, Paragraph (1) of the Basic Agrarian Law.